Tropheryma whipplei endocarditis in Spain: Case reports of 17 prospective cases. Issue 26 (June 2016) - García-Álvarez, Lara; Sanz, María Mercedes; Marín, Mercedes; Fariñas, MªCarmen; Montejo, Miguel; Goikoetxea, Josune; Rodríguez García, Raquel; de Alarcón, Arístides; Almela, Manuel; Fernández-Hidalgo, Núria; Alonso Socas, María del Mar; Goenaga, Miguel Ángel; et al.
Abstract : Abstract: Tropheryma whipplei endocarditis is an uncommon condition with very few series and <90 cases reported in the literature. The aim of the study was to analyze the epidemiological, clinical, and outcome characteristics of 17 cases of T. whipplei endocarditis recruited in our country from a multicentric cohort from 25 Spanish hospitals from the Spanish Collaboration on Endocarditis—Grupo de Apoyo al Manejo de la Endocarditis infecciosa en España. From a total of 3165 cases included in the cohort, 14.2% were diagnosed of blood culture negative endocarditis (BCNE) and 3.5% of these had T. whipplei endocarditis. This condition was more frequent in men. The average age was 60.3 years. Previous cardiac condition was present in 35.3% of the cases. The main clinical manifestation was cardiac failure (76.5%) while fever was only present in the 35.3%. Ecocardiography showed vegetations in 64.7% of patients. Surgery was performed in all but 1 cases and it allowed the diagnosis when molecular assays were performed. A broad range rRNA 16S polymerase chain reaction was used for first instance in all laboratories and different specific targets for T. whipplei were employed for confirmation. A concomitant Whipple disease was diagnosed in 11.9% of patients. All patients received specific antimicrobial treatment for at least 1 year, with no relapse and complete recovery. T. whipplei endocarditis is an uncommon condition with an atypical presentation that must be considered in the diagnosis of BCNE. The prognosis is very good when an appropriate surgical management and antimicrobial-specific treatment is given.